Management of Idiopathic Retroperitoneal Fibrosis, a Retrospective Study at Prince Hussein Urology and Organ transplantation center (PHUO), Jordan (Iranian Journal of Kidney Diseases, 2019)
Introduction. to study the presentation, clinical course, laboratoryresults, imaging findings, medical and urological treatments ofidiopathic retroperitoneal fibrosis at our institution.Methods. Between January 2006 and December 2017, medical recordsand operatives' notes of 116 patients with idiopathic retroperitonealfibrosis (IPRF) were reviewed retrospectively. Diagnosis was doneby clinical and radiological imaging that fulfilled a strict criterion.All patients were initiated on Prednisolone 60 mg for two months,and reduced until reaching 10 mg daily, with a total duration of24 months in the responding patients. Renal drainage was done incases of obstructed kidneys. To assess response, both laboratoryresults and imaging studies at initiation and after 4 months werereviewed and compared.Results. Of 116 patients diagnosed with IRPF, eighty five (73.3%)were male and thirty one (26.7%) female, with mean ± SD age atpresentation was (50.5 ± 10.6) years. 79% of the patients complaintof abdominal and low back pain, 27% uremic symptoms, 10.3% hada new onset of hypertension, 3.4% presented with anejaculation,and 13.8% were totally asymptomatic. Uretric obstruction hadbeen resolved in 132 ureters after a mean of 152 days of treatment.Almost 30 % reduction in the fibrotic mass size was achieved in82 % of patients.Conclusion. Glucocorticoids is the the mainstay of treatment. Therenal function tests, of the vast majority of patients, normalizedwith treatment. Relapse may occur, so a follow-up over a longperiod of time is required. A high index of suspicion is neededfor diagnosis in asymptomatic patients.